Latvijos žiniasklaida naujajame tūkstantmetyje: raidos, turinio ir vartojimo tendencijos bei žiniasklaidos vartotojų bendruomenės atsiradimas - Brikše, Inta; Zelče, Vita (Information & Media, 2008)
Šiame straipsnyje apžvelgiamos Latvijos žinias-klaidos raidos, turinio ir vartojimo tendencijos nuo 2000 m. Straipsnyje remiamasi Latvijos Centrinio statistikos biuro, Latvijos Nacionalinės bibliotekos Bibliografijos instituto, taip pat TNS Latvia rinkos tyrimų kompanijos duomenimis bei Latvijos universiteto Komunikacijos tyrimų katedros atliktomis studijomis. Autoriai apibendrina, jog žiniasklaidos raida bei jos santykis su auditorija yra lankstūs ir gana komplikuoti. Ekonominis augimas sąlygojo Latvijos visuomenės gyvenimo būdo pokyčius, o spartus vartojimo augimas atvėrė galimybes žiniasklaidai įsiveržti į žmonių gyvenimą. Šiame procese žiniasklaidai tenka labai svarbus vaidmuo, siūlant pramogas ir kuriant naujo gyvenimo būdo reprezentacijas.The Latvian media in the new millennium: Trends in development, content and usage and the emergence of a community of media usersInta Brikše and Vita ZelčeSummaryThis article reviews trends in the development, content and usage of the mass media in Latvia since the year 2000. It is based on data from the Central Statistical Bureau of Latvia, the Bibliography Institute of the Latvian National Library, and the TNS Latvia research company, as well as on studies conducted by the Department of Communication Studies of the University of Latvia. The authors conclude that media development, as well as the relationship between the media and their audience, must be seen as flexible and fairly complicated. Economic growth and increasing prosperity among Latvia’s residents have meant changes in lifestyle. There has been an intensive shift toward consumption, and therefore, the media have encroached upon the part of lives that are based on consumerism. In this new lifestyle, the media have a very important role to play – not so much in terms of constructing public or private values, but rather of offering entertainment opportunities and representing the new lifestyle.Keywords: Latvian media, press, TV, radio, Internet, audience, consumerism
Keywords: nėra